1994
DOI: 10.1007/bf01954490
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal proliferation of Epstein-Barr virus-infected T-cells in a patient with virus-associated haemophagocytic syndrome

Abstract: Virus-associated haemophagocytic syndrome (VAHS) is a non-neoplastic, generalized histiocytic proliferation disorder showing marked haemophagocytosis associated with systemic viral infection. We describe the case of a 1-year-old girl with Epstein-Barr virus (EBV)-related VAHS, in whom Southern blot analysis showed monoclonal proliferation of bone marrow cells with the EBV genome; detected with the Xho-1 fragment of the latent infection membrane protein genome. EBV serology showed anti-Epstein-Barr virus nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The majority of previous studies have reported single cases; however, the study by Quintanilla-Martinez et al described the clinicopathological features of 5 cases of this disease (2). In this study, we reviewed the clinicopatho- logical features of 17 cases with systemic EBV-positive T-cell LPD of childhood following acute EBV infection, including the present case (Table I) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). We revealed that clonal systemic proliferation of EBV-infected T-cells that appear morphologically innocuous with an activated cytotoxic phenotype expressing CD8 and/or CD4 is central to the disease.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of previous studies have reported single cases; however, the study by Quintanilla-Martinez et al described the clinicopathological features of 5 cases of this disease (2). In this study, we reviewed the clinicopatho- logical features of 17 cases with systemic EBV-positive T-cell LPD of childhood following acute EBV infection, including the present case (Table I) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). We revealed that clonal systemic proliferation of EBV-infected T-cells that appear morphologically innocuous with an activated cytotoxic phenotype expressing CD8 and/or CD4 is central to the disease.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of published data have confirmed that CD3 + T cells, most often the CD8 + subset, both in tissue biopsies [21,49,51,52,55-57] and circulating lymphocytes [26,58], are the dominant infected population in EBV-HLH. However, unequivocal infection of NK cells has also been observed, and may even be the dominant infected cell type in some patients [59].…”
Section: Ebv-associated Haemophagocytic Lymphohistiocytosismentioning
confidence: 99%
“…There are reports that plasmapheresis [12,17,18], intravenous immunoglobulin (IVIG) [19,20], cyclosporin A (CSA) [21,22], etoposide [3,7,12], and a combination of IVIG and etoposide [23] have been effective. However, there is no consensus in the literature, which of these treatments is optimal [24].…”
Section: Introductionmentioning
confidence: 99%
“…EBV-HLH occurs in both children [7,12] and young adults (defined as older than 15 years of age) [1,[3][4][5][6][8][9][10][11][27][28][29]. It is not clear whether the etoposide therapy would also be effective in young adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation